2018
DOI: 10.1103/physrevd.98.026004
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entanglement entropy decomposition in an anisotropic gauge theory

Abstract: We study holographic entanglement entropy in spatially anisotropic field theory. We observe that for the background considered in this paper, to a good approximation, the holographic entanglement entropy can be decomposed into two terms. One of them is the entanglement entropy of the isotropic field theory at a fixed temperature and the other term is only a function of the anisotropy parameter. Moreover, for large enough values of the anisotropy parameter, our numerical results indicate that the entanglement e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The key to this holographic entanglement entropy asymmetry can be related to the unequal entanglement pressure [58]. Studies of holographic entanglement entropy in spatially anisotropic field theory also showed such asymmetry owing its origin to the fact that the pressure in one direction is different from the others [59]. This is also consistent with the results obtained using the complexity equals action proposal [61].…”
Section: Strip Perpendicular To the Direction Of Boostsupporting
confidence: 79%
“…The key to this holographic entanglement entropy asymmetry can be related to the unequal entanglement pressure [58]. Studies of holographic entanglement entropy in spatially anisotropic field theory also showed such asymmetry owing its origin to the fact that the pressure in one direction is different from the others [59]. This is also consistent with the results obtained using the complexity equals action proposal [61].…”
Section: Strip Perpendicular To the Direction Of Boostsupporting
confidence: 79%
“…The theory flows between two fixed points of the renormalization group, one in the ultraviolet corresponding to a four dimensional N = 4 super Yang-Mills theory, and the other in the infrared where the theory is also conformal but, due to the magnetic field, reduces to 1+1 dimensions. The gravity dual of this theory was presented in [43] and has been used to investigate the effects of an external magnetic field in several physical observables, of which a comprehensive list would be difficult to achieve, but some studies relevant to our current topic are [44][45][46][47][48][49].…”
Section: Jhep09(2018)131mentioning
confidence: 99%
“…In particular, in [41] it was proposed to use the HEE as a probe of confinement. The HEE has been extensively studied and applied in the investigation of the phase transitions in various holographic QCD (HQCD) models [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
mentioning
confidence: 99%